Experimental observations of bubble–particle collisional interaction relevant to froth flotation, and calculation of the associated forces. (1st June 2020) - Li, Shuofu; Schwarz, M. Philip; Yang, William; Feng, Yuqing; Witt, Peter; Sun, Chunbao
Highlights: Particle–bubble collisional attachment is investigated experimentally. Flow configurations that provide larger bubble-particle relative velocity are studied. High speed videos of particle trajectories are recorded and digitally analysed in detail. Forces on particles were determined from experimental trajectories and particle movement explained. Particle-bubble attachment was analyzed in terms of sliding time. Abstract: This paper modifies an experimental system previously used by Verrelli et al. to investigate particle–bubble attachment. Three different flow configuration cases were studied to investigate the effects of flow environment on the particle–bubble interactions and to model a situation more characteristic of real industrial froth flotation processes. The three configurations are as follows: particles dropped onto a bubble held stationary at the tip of a capillary tube; particles in water flowing past a bubble held stationary; and particles dropped onto a bubble rising freely. This is the first time collisional interaction between a freely rising bubble and hydrophobized glass ballotini particles has been studied in detail. The present work has shown the importance of considering real flow situations when modelling bubble–particle interactions for flotation applications. According to the results, there are more particles swept off the bubble surface before reaching the 90° position from the vertical axis under conditions of liquid flow (either because of externally generated flow or because of bubble rise), compared to the case where the bubble is stationary in a stationary liquid. This appears to suggest that attachment probability is reduced when liquid flows past the bubble. Extracting values of the individual force components provides greater insight into the mechanisms influencing the particle's behavior as it interacts with the bubble. Comparison of particle trajectories that resulted in attachment with those that did not, provides further evidence in support of the proposition that contact time needs to be longer than induction time for attachment to occur.